Research of Transmission Error Modeling and Its Parameter Sensitivity of the Cable-driven Sheave - Xu Chuntian; Wang Peng (Jixie chuandong)
The synchronous accuracy of cable-driven sheaves is a key technology for the rendezvous and docking of two spacecrafts. And how difficult it is guaranteed can be reflected by parameter sensitivity. To obtain parameter sensitivity to transmission error of cable-driven sheaves,a prediction model for their transmission error is firstly built based on cable deformation in their driving process and the factors influencing on transmission error are determined. Then,in view of the complicated nonlinear relations between the parameters and transmission error of the cable-driven sheaves,a method for fitting data with an exponential curve is proposed,by which this model is simplified as relations between the transmission error and single factor. And the equation for parameter sensitivity is established. Finally,the parameter sensitivity effects on transmission error of the cable-driven sheaves are analyzed. This can provide a reference in effective controlling the synchronous accuracy of the spacecraft docking and in improving their assembly efficiency.